2012
DOI: 10.4067/s0717-95022012000300053
|View full text |Cite
|
Sign up to set email alerts
|

Study of Undescended Testes by High Frequency Ultrasound

Abstract: SUMMARY:Undescended testes or cryptorchidism in the most common congenital anomaly of male reproductive system. The descent is multifactorial with gubernaculums playing major role. The failure of descent can be at trans-abdominal or inguino-scrotal phase. Locating undescended testes is important in view of low fertility and high rate of occurrence of neoplasm in them. Ultrasound is the standard imaging technique of choice in children with a non-palpable testis as it is non-invasive and does not use ionizing ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A prevalence study conducted at the University Teaching Hospital in Lusaka on 384 deceased adults showed that only one deceased adult presented with a right-sided impalpable testis [27]. In a study by Onkar et al about undescended testes using high-frequency ultrasound which incorporated 41 boys, 30 patients had unilateral and 11 had bilateral undescended testes [28]. The prevalence was more on the right side (16 out of 30) and 26 (63%) were located in the inguinal canal [28].…”
Section: Discussionmentioning
confidence: 99%
“…A prevalence study conducted at the University Teaching Hospital in Lusaka on 384 deceased adults showed that only one deceased adult presented with a right-sided impalpable testis [27]. In a study by Onkar et al about undescended testes using high-frequency ultrasound which incorporated 41 boys, 30 patients had unilateral and 11 had bilateral undescended testes [28]. The prevalence was more on the right side (16 out of 30) and 26 (63%) were located in the inguinal canal [28].…”
Section: Discussionmentioning
confidence: 99%
“…40 Secondly, the dog spleen differs from rodent and human spleen in that it can store large amounts of blood for rapid release in an emergency. 41 Either or both of these scenarios would lead to the high spleen uptake in dogs observed by Welch. Notably, we expect this will not be an issue in human studies with 68 Ga-labeled erythrocytes, which we expect to be similar to blood pool imaging using 99m Tc-based radiotracers.…”
Section: Washed 68 Ga-labeled Erythrocytes Micropet Imaging In Ratmentioning
confidence: 98%
“…Onkar et.al identified that the bearings contamination of lubricant grease by solid particles the contaminant is added in the lubricant even in a small amount, there is increase in amplitude of vibration signal [2]. Vital Rao et.al identified that vibration spectrum don't give clarity in peak rising in defect frequency where the acoustic emission is superior to vibration in diagnose the defect in bearings [3].…”
Section: Introductionmentioning
confidence: 99%